Phenobarbital and Phototherapy Combination Enhances Decline of Total Serum Bilirubin and May Decrease the Need for Blood Exchange Transfusion in Newborns with Isoimmune Hemolytic Disease - Kaabneh, Mahmoud AF (Clin Med Insights Pediatr, 2015)
OBJECTIVE: The objective of this study was to evaluate the effect of phenobarbital and phototherapy combination on the total serum bilirubin of the newborn infants with isoimmune hemolytic disease (IHD) and its impact on blood exchange transfusion rates. PATIENTS AND METHOD: This single-blinded, prospective, randomized, controlled trial was conducted between March 2013 and December 2014 at the pediatric ward of two Military Hospitals in Jordan. A total of 200 full-term neonates with IHD were divided randomly into two groups: (1) the phenobarbital plus phototherapy group (n = 103), and (2) the phototherapy-only group (n = 97). Infants in group 1 received an oral dose of 2.5 mg/kg phenobarbital every 12 hours for 3 days in addition to phototherapy. The total serum bilirubin was observed. RESULTS: Of the total 200 included newborn infants, 186 infants completed the study: 97 infants were included in group 1 and 89 infants in group 2. The difference between the mean total serum bilirubin levels at 24, 48, and 72 hours after starting the trial was clinically and statistically significant at P < 0.05. The differences between the two groups were also statistically significant at P < 0.05. Of the total 186 who completed the study, only 22 underwent blood exchange transfusion [7 from group 1, and 15 from group 2 (P = 0.0478)]. CONCLUSION: In a limited-resources setting, phenobarbital in combination with phototherapy may be helpful to newborn infants with IHD, as it results in a faster decline in total serum bilirubin, thus decreasing the need for blood exchange transfusion than phototherapy alone.